Diagnosis of Accommodative Spasm Aided by Handheld Photoscreener. Issue 1 (2nd January 2020) - Lind, Taylor; Atkinson, Scott; Marsh, Justin D.
ABSTRACT: We report a case of accommodative spasm in an 8-year-old girl discovered by handheld photoscreener. The patient was found to have a Chiari I malformation, and managed with atropine drops and reading glasses, ultimately with improvement in her symptoms. We believe this to be the first case of accommodative spasm diagnosis aided by the use of a handheld photoscreener.